Studies of H2 storage efficiency of metal-doped carbon nanotubes by optical adsorption spectra analysis - Itas, Yahaya Saadu; Khandaker, Mayeen Uddin *; Suleiman, Abdussalam Balarabe; Ndikilar, Chifu E.; Lawal, Abdullahi; Razali, Razif; Idowu, Ismail Ibrahim; Danmadami, Amina Muhammad; Yamusa, Aminu Shehu; Osman, Hamid; Idris, Abubakr M. (Diamond and Related Materials, 2023)
Due to the recent demands to replace fossil fuels with hydrogen, researchers are making many attempts to develop new materials to store hydrogen energy. Hydrogen is considered a potential candidate to replace fossil fuels due to its non-toxic, massless, and more efficient properties. This research has investigated the enhancement of the hydrogen storage capabilities of armchair single-walled carbon nanotubes (SWCNTs) through the separate doping of transition metals such as osmium (Os) and iron (Fe). The studies were performed with quantum simulation codes implemented in Quantum ESPRESSO and thermo_pw based on density functional theory (DFT), plane waves and pseudopotentials. The obtained results show that Os-doped SWCNTs are more suitable for H2 storage than Fe-doped SWCNTs due to the almost equal energy loss with and without H2 adsorption. Furthermore, lower adsorption in perpendicular directions indicated that the adsorbed H2 molecules aligned parallel to the nanotube axes. This further confirmed that the SWCNT nanotube system had a higher aspect ratio in parallel directions. Overall, it has been observed that transition metal doping increases the efficiency of the hydrogen storage potential of armchair SWCNTs compared to other doped metals. In general, the co-doping of SWCNT with osmium and nitrogen atoms increases the adsorption capability of H2 molecules.